Actin crosslinking by α-actinin averts viscous dissipation of myosin force transmission in stress fibers - Katsuta, Hiroki; Okuda, Satoru; Nagayama, Kazuaki; Machiyama, Hiroaki; Kidoaki, Satoru; Kato, Masashi; Sokabe, Masahiro; Miyata, Takaki; Hirata, Hiroaki (iScience, 2023)
Contractile force generated in actomyosin stress fibers (SFs) is transmitted along SFs to the extracellular matrix (ECM), which contributes to cell migration and sensing of ECM rigidity. In this study, we show that efficient force transmission along SFs relies on actin crosslinking by α-actinin. Upon reduction of α-actinin-mediated crosslinks, the myosin II activity induced flows of actin filaments and myosin II along SFs, leading to a decrease in traction force exertion to ECM. The fluidized SFs maintained their cable integrity probably through enhanced actin polymerization throughout SFs. A computational modeling analysis suggested that lowering the density of actin crosslinks caused viscous slippage of actin filaments in SFs and, thereby, dissipated myosin-generated force transmitting along SFs. As a cellular scale outcome, α-actinin depletion attenuated the ECM-rigidity-dependent difference in cell migration speed, which suggested that α-actinin-modulated SF mechanics is involved in the cellular response to ECM rigidity. [Display omitted] •Actin crosslinking by α-actinin solidifies stress fibers (SFs)•Inhibition of α-actinin crosslinking induces actin and myosin flows along SFs•SF fluidization diminishes transmission of myosin-generated force along SFs•α-Actinin is essential for rigidity-dependent regulation of cell migration speed Biological sciences; Cell biology; Biophysics